Організаційна структура сучасної форми парламенської культури - Ломжець, Ю. В.; Ломжец, Ю. В.; Lomzhec, Y. (My University, 2010)
In given article analysis of organizing structured element forms of the parliamentary culture is conducted. It is given notion of the parliamentary culture, its nature and contents are studied. Parliamentary culture is considered as intrinsically measurement of politics – as system of glance, beliefs, valuables in consciousness and behaviour of the people.
Ломжець Ю. В. Організаційна структура сучасної форми парламенської культури / Ю. В. Ломжець // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 283-294.
Keywords: організаційна структура сучасної форми парламентської культури; система поглядів, переконань, цінностей в свідомості і поведінці громадян; организационная структура современной формы парламенской культуры; система взглядов, убеждений, ценностей в сознании и поведении граждан; the organizational structure of the modern form of the Parliamentary Culture; system of attitudes, beliefs, values and behavior in the minds of citizens